Robot-assisted radical cystectomy versus open radical cystectomy in patients with bladder cancer (RAZOR): an open-label, randomised, phase 3, non-inferiority trial. Issue 10139 (23rd June 2018) - Parekh, Dipen J; Reis, Isildinha M; Castle, Erik P; Gonzalgo, Mark L; Woods, Michael E; Svatek, Robert S; Weizer, Alon Z; Konety, Badrinath R; Tollefson, Mathew; Krupski, Tracey L; Smith, Norm D; Shabsigh, Ahmad; et al.
Summary: Background: Radical cystectomy is the surgical standard for invasive bladder cancer. Robot-assisted cystectomy has been proposed to provide similar oncological outcomes with lower morbidity. We aimed to compare progression-free survival in patients with bladder cancer treated with open cystectomy and robot-assisted cystectomy. Methods: The RAZOR study is a randomised, open-label, non-inferiority, phase 3 trial done in 15 medical centres in the USA. Eligible participants (aged ≥18 years) had biopsy-proven clinical stage T1–T4, N0–N1, M0 bladder cancer or refractory carcinoma in situ. Individuals who had previously had open abdominal or pelvic surgery, or who had any pre-existing health conditions that would preclude safe initiation or maintenance of pneumoperitoneum were excluded. Patients were centrally assigned (1:1) via a web-based system, with block randomisation by institution, stratified by type of urinary diversion, clinical T stage, and Eastern Cooperative Oncology Group performance status, to receive robot-assisted radical cystectomy or open radical cystectomy with extracorporeal urinary diversion. Treatment allocation was only masked from pathologists. The primary endpoint was 2-year progression-free survival, with non-inferiority established if the lower bound of the one-sided 97·5% CI for the treatment difference (robotic cystectomy minus open cystectomy) was greater than −15 percentage points. The primary analysis was done in the per-protocol population. Safety was assessed in the same population. This trial is registered withClinicalTrials.gov, numberNCT01157676 . Findings: Between July 1, 2011, and Nov 18, 2014, 350 participants were randomly assigned to treatment. The intended treatment was robotic cystectomy in 176 patients and open cystectomy in 174 patients. 17 (10%) of 176 patients in the robotic cystectomy group did not have surgery and nine (5%) patients had a different surgery to that they were assigned. 21 (12%) of 174 patients in the open cystectomy group did not have surgery and one (1%) patient had robotic cystectomy instead of open cystectomy. Thus, 302 patients (150 in the robotic cystectomy group and 152 in the open cystectomy group) were included in the per-protocol analysis set. 2-year progression-free survival was 72·3% (95% CI 64·3 to 78·8) in the robotic cystectomy group and 71·6% (95% CI 63·6 to 78·2) in the open cystectomy group (difference 0·7%, 95% CI −9·6% to 10·9%; pnon-inferiority =0·001), indicating non-inferiority of robotic cystectomy. Adverse events occurred in 101 (67%) of 150 patients in the robotic cystectomy group and 105 (69%) of 152 patients in the open cystectomy group. The most common adverse events were urinary tract infection (53 [35%] in the robotic cystectomy group vs 39 [26%] in the open cystectomy group) and postoperative ileus (33 [22%] in the robotic cystectomy group vs 31 [20%] in the open cystectomy group). Interpretation: In patients with bladder cancer, robotic cystectomy was non-inferior to open cystectomy for 2-year progression-free survival. Increased adoption of robotic surgery in clinical practice should lead to future randomised trials to assess the true value of this surgical approach in patients with other cancer types. Funding: National Institutes of Health National Cancer Institute.